Strategi Pemasaran yang Mempengaruhi Keputusan dalam Pembelian Asuransi - Farah Aulia Ernawati; Theresia Naomi Putri Manurung (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
This study aims to analyze marketing strategies that affect consumers' decisions on insurance purchases. In the competitive insurance industry, a deep understanding of the factors affecting consumer purchasing behavior is essential for companies to devise effective marketing strategies. The research methods used include surveys of insurance consumers as well as analysis of secondary data from related literature. Research results show that several marketing strategies, such as discount offers, loyalty programs, product personalization, and digital marketing, have a significant impact on consumer purchasing decisions. In addition, factors such as brand confidence, service quality, and company reputation also play an important role. This study suggests that insurers should focus on innovating in their marketing strategies, prioritizing transparency, and establishing long-term relationships with customers to increase insurance purchase rates. Thus, a comprehensive understanding of effective marketing strategies can help insurance companies increase market share and customer satisfaction.